(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Objective- Osteoarthritis is a heterogenous disease affecting synovial joints of hands, knees, hips and spine and is characterized by progressive degeneration of articular cartilage with a progressive episodic synovitis and bone remodeling. Phytosterols are plant based cholesterol which have proven to show numerous therapeutic benefits. Therefore this study was conducted to determine the anti-osteoarthritis effect of phytosterols using MG-63 cell line for in-vitro analysis as well as in-silico methods were being used.Methodology- In-silico and in-vitro studies were conducted using computational methods to predict the pharmacokinetic parameters and biological activity of the phytosterols. MG 63 cell line was used in order to assess their response toward phytosterol treatment. Online servers such as pkCSM, OSIRIS, Molinspiration, Swiss ADME were being used in order to assess the physiochemical, pharmacokinetic and pharmacological property of the compound.Result- The in-silico and in-vitro methods used for analysis determined a wide range of results which provides enough evidence regarding anti-osteoarthritic effect of phytosterols. Stigmasterol has shown anti-eczematic, lipid peroxidase inhibition, immunosuppression, nootropic and bone disease treatment activity whereas β-sitosterol has shown chemoprotective, hepatoprotective, lipid peroxidase inhibition and bone disease treatment activity.Conclusion- Therefore this study provides evidence which shows light on effectiveness of phytosterol for management of osteoarthritis and also towards the response of MG-63 cell line toward phytosterol treatment and this could be utilized for further studies related to the topic